Randomised controlled pilot trial on feasibility, safety and effectiveness of osteopathic MANipulative treatment following major abdominal surgery (OMANT pilot trial). (June 2016) - Probst, Pascal; Büchler, Elena; Doerr-Harim, Colette; Knebel, Phillip; Thiel, Bettina; Ulrich, Alexis; Diener, Markus K.
Abstract: Background: Postoperative complications are a major concern after gastrointestinal surgery. Resolving movement restrictions such as postoperative paralysis, osteopathic manipulative treatment (OMT) may be beneficial. The OMANT pilot study was the first prospective trial to investigate the feasibility, safety and potential benefits of OMT after gastrointestinal surgery. Methods/Design: Twenty patients with elective bowel resection were randomised in two parallel groups. Patients in the intervention group received standard care with the addition of OMT on postoperative days 1–5. Results: OMANT pilot was conducted between February and April 2015. Of 38 patients invited, only 2 (5.3%) were unwilling to participate in the trial. OMT was conducted successfully in 49 of 50 attempts (98%). OMT patients showed lower postoperative morbidity than control patients (comprehensive complication index 30.8 vs. 37.1). Pain during the postoperative course was decreased significantly by OMT. Conclusions: Evaluation of OMT in a prospective clinical trial is feasible, and OMT is safe in postoperative patients. Since OMT is a pain-relieving and well tolerated treatment in surgical patients, it might be beneficial after gastrointestinal surgery, and its effectiveness should be evaluated in an affirmative RCT based on this pilot trial.